Alkali and sulfate effects on mechanical properties and microscopic mechanisms of slag and fly ash geopolymers - Miaomiao Gong; Ao Shen; Yiyi Wang; Haoran Lin; Rui He (Scientific Reports)
Abstract Aiming at the problem that it is difficult to realize low-cost, high-performance and large-scale utilization of cementitious materials prepared from bulk solid wastes, this paper constructs a set of composite cementitious system based on alkaline activation of slag and fly ash (FA) by calcium carbide slag (CCS) and synergistic activation of sodium sulfate (Na2SO4) as a chemical dopant. The influence of factors such as solid waste type, mixing ratio, and Na2SO4 content on the mechanical properties of composite cementitious systems was investigated by assessing compressive strength and analyzing microstructure using XRD, SEM-EDS, and FTIR. The test results indicate that CCS and Na2SO4 exert significant influences on the strength of the composite cementitious system. CCS acts as an alkali activator, enhancing the system’s hydration with an optimal dosage of 25%. Low Na2SO4 content also promotes hydration, but higher concentrations disrupt the internal structure of the cementitious system post-coagulation, with an optimal content of 6%. The Projection Pursuit Regression (PPR) strength prediction model can fit the actual experimental data very well, which provides a feasible method for the proportion design and mechanical strength prediction of all-solid-waste cementitious systems.